The Pengaruh Faktor Fundamental dan Risiko Sistematik Terhadap Harga Saham pada Perusahaan Sektor Ritel yang Terdaftar di Bursa Efek Asean-5 Tahun 2021-2023 - Revalina Dwi Adelia; Rulyanti Susi Wardhani; Julia Julia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The capital market is a means for companies to obtain funds from the public through the stock market. Capital markets in the ASEAN region provide new opportunities for investors in ASEAN countries and create opportunities for foreign market stock exchanges. This research aims to examine the influence of fundamental factors and systematic risk on stock prices listed on the Asean-5 Stock Exchange. The sampling technique uses a purposive sampling method. The population of this research is all retail sector companies listed on the ASEAN-5 Stock Exchange with a population of 121 and a sample of 23 companies. Based on research results, return on assets has a positive effect on stock prices, earnings per share have a negative effect on stock prices, debt to equity ratio has a negative effect on stock prices, price earnings ratio has a negative effect on stock prices, and systematic risk has a negative effect on the stock prices of retail sector companies.